Integrated approach to treatment of a multidrug-resistant bacterial infection in Geoffroy’s side-necked turtle (Phrynops geoffroanus) - Domiciano, Nicole de Jesus; Cabalero , Rafael de Carvalho; Melo, Raphael Libório Ribeiro; de Sousa, Lara Carvalho Alves; dos Santos, Estela Larissa Silva; Bittencourt, Marta Vasconcelos; Moroz, Ludmila Rodrigues; Ferreira, Paulo Roberto Bahiano (Journal of Wildlife and Conservation Medicine, 2026)
Background Opportunistic bacterial infections of the shell and plastron are one of the main causes of diseases affecting Testudines, frequently associated with high levels of environmental bacterial contamination. Objective This case report describes the clinical presentation, diagnosis and treatment of a multidrug-resistant bacterial infection in a Geoffroy’s side-necked turtle (Phrynops geoffroanus). Case description A female Geoffroy’s side-necked turtle, under ex situ management, presented a greenish-yellow, necrotic lesion in the abdominal and femoral scutes region on the right side of the plastron during the annual clinical evaluation. Examination and diagnosis Physical examination revealed the presence of keratolysis and a malodorous content. The clinical suspicion of an abscess was confirmed by video-assisted exploration of the coelomic cavity. Multidrug-resistant Pseudomonas aeruginosa (MDR-PA) and Proteus mirabilis (MDR-PM) were identified through bacteriological analyses. Treatment/therapies In addition to surgical intervention, six treatment cycles were established until the patient’s clinical discharge. The therapeutic protocols included courses of antibiotics, pain management, multivitamins, fluid therapy, as well as wound cleansing. Antibiotic therapy was adjusted according to antibiogram tests, and in the final stages of healing, weekly sessions of low-level laser therapy were conducted. Conclusion This case highlights the importance of using bacterial isolation and antibiogram tests as a reference for managing and resolving clinical cases. Through an integrated approach, the need for continuous clinical reassessment and therapeutic adjustments are always considered during the process, as well as nutritional and environmental management as part of the complete treatment.